GIVING QUESTION AND GETTING ANSWER (GQGA) LEARNING MODEL ON STUDENTS CIVIC SKILLS IN CIVICS LESSONS IN PRIMARY SCHOOLS - Nindy Putri Sabrina; Reza Rachmadtullah (Media Inovasi Pendidikan dan Publikasi, 2024)
Examining how the Giving Question and Getting Answer (GQGA) paradigm impacts elementary school children' civic skill development is the primary goal of this research. Fifty fourth graders from two different State Elementary School classes participated in this study. One group, IV B, used the GQGA technique for instruction, while the other group, IV A, stuck with the tried-and-true method. A posttest comprehension tool was utilized for data collecting. Using a posttest-only control group design, this study employs a quantitative research strategy reminiscent of quasi-experimental research. The t-test, which had before checked for normality and homogeneity, is utilized as the data analysis approach. According to the findings of the SPSS 20 Independent Sample t-test, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted; this indicates that the GQGA learning model has an effect on elementary school students' civic skills.